Hubungan Status Gizi Masyarakat dengan Kesiapan Beradaptasi dengan COVID-19 - Pricilia Dewi Sulistyawati; Desmawati (LPPM Hang Tuah Pekanbaru, 2022)
The COVID-19 pandemic has hit all countries in the world, including Indonesia. Various shapes of prevention such as maintenance of nutritional status is an important thing that needs attention. This study aims to see the relationship between the nutritional status of the community and readiness to adapt to COVID-19. This study uses a sectional, which was carried out to the community in a RW in the Pamulang area, Banten in December 2021-March 2022 with a sample of 231 people who were selected according to the inclusion criteria. The dependent variable of this study is readiness to adapt to COVID-19, while the independent variable of this study is the nutritional status of the community. Collecting data using a questionnaire that has been tested for validity and reliability with a Cronbach's alpha value of 0.854 > 0.361 with a total of 30 samples so that it can be declared reliable. Data that obtained in this study were analyzed as univariately using descriptive statistics and bivariate analysis using the Chi-Square test with the results showing that poor nutritional status 34.2% and good nutritional status 65.8%, for respondents who are ready to adapt 78.4 % and not ready to adapt 21.6%. There is a significant relationship between public nutritional status and readiness to adapt to COVID-19 (p value = 0.000 and OR 3.244).